How do new mobility practices emerge? : A comparative analysis of car-sharing in cities in Norway, Sweden and the Netherlands - Svennevik, Elisabeth M.C.; Dijk, Marc; Arnfalk, Peter (Energy Research & Social Science, 2021)
The hegemony of the private car is increasingly challenged as new policies and technologies affect passenger mobility. This study investigates how car-sharing is emerging and unfolding amidst established urban mobility practices. We apply a conceptual framework with seven elements based on social practice theories and transition literature to deconstruct practices in order to reveal how such (relatively) new mobility practices emerge. Our comparative study uses qualitative methods with data from 58 household interviews and three half-day workshops with stakeholders in Oslo, Norway; Malm¨o, Sweden; and Rotterdam, the Netherlands. The research question asks how car-sharing practices unfold differently in different places. The results indicate how elements of mobility practices change from the situation before and without car-sharing to after and with car-sharing. The analysis reveals different changes in the three areas, with greater change in Malmö because of public procurement of car-sharing and less in Rotterdam, where there was interest in urban experiments directed at phasing out car use and supporting car-free city zones. The framework highlights that new digital technologies and regulations are important, influencing business models and the social meaning of mobility towards a broader acceptance of access-based transportation. For car-sharing to contribute to environmental sustainability, the three areas need to reduce the daily use of cars so car-sharing can become a viable option for occasional use of cars. Further, policies should combine Electric Vehicles (EVs) and car-sharing, e.g. in Oslo, the focus of promoting EVs should include shared EVs, and in Rotterdam, improved charging infrastructure would be effective.
Keywords: Social practice theories; sustainable mobility; Sustainability transition studies; Car-sharing; shared mobility